2017
DOI: 10.1038/srep43833
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and reliable establishment of lymphoblastoid cell lines by Epstein-Barr virus transformation from a limited amount of peripheral blood

Abstract: Lymphoblastoid cell lines (LCLs) transformed by Epstein-Barr virus (EBV) serve as an unlimited resource of human genomic DNA. The protocol that is widely used to establish LCLs involves peripheral blood mononuclear cell isolation by density gradient centrifugation, however, that method requires as much as 5 ml of peripheral blood. In this study, in order to provide a more simple and efficient method for the generation of LCLs, we developed a new protocol using hemolytic reaction to enrich white blood cells for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Studies have shown that chronic activation of STAT3 is thought to be triggered by IL-6, which is induced by persistent activation of NF-κB [ 87 , 88 ]. Activation of NF-κB and STAT3 following B lymphocyte infection with EBV in vitro leads to the induction of chronic inflammation, which is critical for the continuous proliferation of infected B cells and the establishment of lymphoblastoid cell lines (LCLs) [ 89 , 90 ]. During this latency, known as latency type III, a total of nine genes are expressed, including EBV-encoded RNAs (EBER 1 and 2), EBV nuclear antigens (EBNAs 1, 2, 3A, 3B, 3C, and LP) and EBV latent membrane proteins (LMPs 1, 2A, and 2B).…”
Section: Role Of Csms In the Induction Of Inflammation During Ebvmentioning
confidence: 99%
“…Studies have shown that chronic activation of STAT3 is thought to be triggered by IL-6, which is induced by persistent activation of NF-κB [ 87 , 88 ]. Activation of NF-κB and STAT3 following B lymphocyte infection with EBV in vitro leads to the induction of chronic inflammation, which is critical for the continuous proliferation of infected B cells and the establishment of lymphoblastoid cell lines (LCLs) [ 89 , 90 ]. During this latency, known as latency type III, a total of nine genes are expressed, including EBV-encoded RNAs (EBER 1 and 2), EBV nuclear antigens (EBNAs 1, 2, 3A, 3B, 3C, and LP) and EBV latent membrane proteins (LMPs 1, 2A, and 2B).…”
Section: Role Of Csms In the Induction Of Inflammation During Ebvmentioning
confidence: 99%
“…A large part of our current understanding of the biology of EBV is based on in vitro studies of infection of human B-lymphocytes. In vitro infection of B-cells leads to their immortalization 1 . In these cells, the virus establishes a latent infection, in which upto 11 viral products, namely 6 Epstein-Barr nuclear antigens (EBNA1, EBNA2, EBNA3a, EBNA3b, EBNA3c, EBNA-LP), 3 latent membrane proteins (LMP1, LMP2a, LMP2b) and large quantities of two non-protein encoding RNAs (EBER-1 and EBER-2) are expressed 2 .…”
Section: Introductionmentioning
confidence: 99%
“…EBV infects B-cells and could immortalize the B-cells and form long-term growing LCLs which consistently express the viruses [4]. This method has been used in laboratories to immortalize certain human blood-derived B-cells which can be later on used as a culture model for various studies including large-scale drug library screening, vaccine study, and high throughput biological studies [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, researchers have put in effort to improve the immortalization method and its efficiency [7]. Recently, it has been shown that with a minor modification, LCLs could be generated from a small volume of peripheral blood as low as 0.1mL [4]. This finding is particularly useful under a circumstance in which the sample volume is limited.…”
Section: Introductionmentioning
confidence: 99%